Isolation and characterization of Lentilactobacillus diolivorans: a high n-propanol-producing microorganism from Baijiu brewing - Zhang, Enhua; Gao, Ruijie; Zhu, Kai; Liu, Pulin; Liao, Weifang; Yang, Tuanyuan; Liang, Xiaotong; Yang, Menglu; Ming, Yingying; Miao, Lihong (Frontiers in Microbiology, 2025)
It is now understood that n-propanol, a higher alcohol constituent in Baijiu, significantly impacts its overall quality. Excessive levels can impart a spicy and bitter taste, necessitating strict control. Despite its importance, the precise mechanism underlying the production of high-content n-propanol in Baijiu brewing and the specific microorganisms responsible for this process remain unclear. This study isolated Lentilactobacillus diolivorans ZX6, known for its high n-propanol production, from Baijiu fermented grains using a modified MRS (SMRS) enrichment medium and gas chromatography detection. The pure strain ZX6 produced 4,399 mg/L of n-propanol in SMRS medium. Using the key enzyme gene sequence for 1,2-propanediol metabolism in L. diolivorans, we designed primers and established a quantitative PCR method to quantify L. diolivorans in first-round fermented grains from three different sauce-flavor Baijiu distilleries. The widespread presence of L. diolivorans in sauce-flavor Baijiu fermented grains indicates its potential role as one of the key microorganisms responsible for the high concentrations of n-propanol. L. diolivorans ZX6 directly utilized glucose fermentation to produce large amounts of n-propanol. High n-propanol synthesis from L. diolivorans ZX6 required high sugar concentrations, anaerobic conditions, and extended fermentation times. Transcriptome analysis revealed that pyruvate and lactic acid, likely major precursors, could enter the methylglyoxal pathway under the catalysis of lactaldehyde dehydrogenase, respectively. These compounds were subsequently metabolized to 1,2-propanediol and then to n-propanol. These findings provide insights into identifying n-propanol-producing microorganisms and establish a theoretical basis for elucidating the high-yield n-propanol mechanism in Baijiu brewing, along with strategies for regulating its content.